Aboral brooding in the deep water sea star Ctenodiscus australis Lütken, 1871 (Asteroidea) from the Southwestern Atlantic - Rivadeneira, Pamela Ruth (2017)
Different stages of development and growth were found in the dorsal surface under the paxillae of Ctenodiscus australis. The maximum number of broods found per specimen was 73 and in some cases different stages were observed on the same female. Oocytes were present in females of all months sampled and were diverse in size (120–850 µm in diameter). Continuous presence and variation in size and stage were also observed in the broods. The typical developmental stage resembles a modified brachiolaria. All these observations suggest continuous reproduction in this deep water species and it also provides new information about reproduction in the Ctenodiscidae family.